Devolução de crianças: a outra face da adoção: um estudo do fenômeno da devolução de crianças e adolescentes no estágio de convivência. - Speck, Sheila (2019)
This thesis is one more effort to analyze the "return phenomenon" in the cohabitation stage , considering the reasons of the adopters for the return and its effects on children and adolescents. We understand that knowledge of risks and the evaluation of the different levels of the adoption process can provide interventions that reduce the failures in the construction of the new bonds. The objective is to analyze the phenomenon by the psychic view, taking into account the complexity of the adoptive filiation. We hypothetize that the adoption tends to fail in the following cases: there is no true desire on the part of the adopter to have a child (some demands may be characterized as perverse); the child does not correspond to the child imagined or fantasized by the parents (consider a certain tension between the desire of procreating and the one of adopting); there is a search for reparation by the adoption; the parental imagos inscribed in the child interfere in the process of filiation; there is a failure on the part of the institutional teams in the evaluation of the applicants , in the follow up of the cohabitation stage and or in the preparation of the children. Based on the methodological proposition of metapsychology, we guided the research by the construction of 10 cases of children and adolescent based on the dossiers, on the juridical processes (dismissal, habilitation and adoption) and on the interviews with children's home teams. In that context, the interface of psychoanalysis with the law allowed for a better understanding and broad reflection on the subject. We have supported our study in Lacan's teaching : desire is essential in the construction of the link with the other. It should be pointed out that despite the many advances in the field of adoption, there is still much to be achieved , especially on the issue of transforming children and adolescents into subjects of rights, as a paradigm change.